Upaya Pengembangan Sistem Pengelolaan Keuangan Pabrik Tahu PT. TSJ Yang Bersifat Manual Menggunakan â€œAutomatic Excellent Data Validationâ€ - Yossy Dumos Herawati; Denada Oktaviani; Mawarni Dyah Nur Halaefi; Rangga Seto Hutomo; Dimas Ido Nofiyanto; Nurma Tambunan (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
Preparation of a comprehensive budget is very important for every company, because it will provide benefits in the form of a systematic approach to management policies, as well as facilitate quantitative evaluation of the company's ultimate goals. This study aims to determine and compile a comprehensive budget calculation as a means of internal control in "Tofu Production House UKM". This type of research uses a quantitative method to determine sales data of tofu products, namely white tofu and yellow tofu in the last 5 months, as well as costs in the production process, both direct and indirect costs. The results of the study show that in the process of compiling a comprehensive budget for â€œTofu Production House UKMâ€ this method is still used which is very simple and does not pay much attention to the costs incurred as a result of the production process. This can be seen from the results of the preparation of a comprehensive budget. From this research, it is hoped that it can be used as a means of controlling and managing the finances of "Tofu Production House UKM" by making a comparison between the comprehensive budget and its realization.